2017
DOI: 10.1021/acs.jpcb.7b00359
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Mixed Lipid Bilayers with Sphingomyelin, Glycerophospholipids, and Cholesterol

Abstract: The highly diversified composition of lipid bilayers across living cells is crucial for many biological processes. Lipid bilayers mainly consist of phosphatidylcholines (PC), phosphatidylethanolamines (PE), sphingomyelin (SM), and cholesterol, with eukaryotic membranes containing high percentage of sphingomyelin and cholesterol. In this study, we have modeled bilayers with different concentration of PC, PE, and SM to understand the changes in bilayer properties with varied SM concentrations. In addition, membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 76 publications
12
51
0
Order By: Relevance
“…Lipid order parameters as a function of protein concentration (SI Appendix, Fig. S33) were found to be very similar values to previous results for pure POPC-sphingomyelincholesterol mixtures with the same force field that was used here (48). Protein concentration had virtually no effect, indicating that the internal structure and dynamics of the lipid bilayer and the liquid-ordered state expected for the lipid composition in this study are not affected by the presence of the proteins.…”
Section: Significancesupporting
confidence: 87%
“…Lipid order parameters as a function of protein concentration (SI Appendix, Fig. S33) were found to be very similar values to previous results for pure POPC-sphingomyelincholesterol mixtures with the same force field that was used here (48). Protein concentration had virtually no effect, indicating that the internal structure and dynamics of the lipid bilayer and the liquid-ordered state expected for the lipid composition in this study are not affected by the presence of the proteins.…”
Section: Significancesupporting
confidence: 87%
“…The FF has also been tested with lipid mixtures containing cholesterol with glycerophospholipids and/or sphingolipids, and agrees with X-ray form factors and NMR order parameters. 1013 This has allowed for accurate interpretations of liquid ordered/disordered phases of lipid mixtures 14 and lipid composition effects on hydrogen bonding and lipid clustering. 12, 13 Although simulations with the C36 lipid FF have been successful, the FF does have inherent flaws.…”
Section: Introductionmentioning
confidence: 99%
“…Several extensive MD studies have shown that their presence affects the packing and thickness of the membrane, as well as its phase-transition temperature [69]. At certain concentrations, CHL and SM increase lipid ordering and decrease surface area, consequently increasing membrane condensation [10]. These effects were also found by MD studies to modulate transport properties, e.g., the permeability of small molecules, even nonpolar gases, through a lipid bilayer [11] and membrane dipole potentials [12].…”
Section: Heterogeneous Lipid Composition Of Biological Membranesmentioning
confidence: 99%